PENGARUH MANAJEMEN LABA TERHADAP TINGKAT OVERSUBSCRIPTION PADA UMKM YANG MELAKUKAN INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA (Studi Empiris pada UMKM yang Terdaftar Tahun 2018-2020 di Bursa Efek Indonesia) - Agnes Charisika Waluyo; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of accrual earnings management (short term discretionary accrual and long term discretionary accrual), real earnings management (abnormal cash flow operations and abnormal discretionary expense), as well as IPO indicators such as underpricing on the oversubscription level of IPOs for SMEs in Indonesia. This research refers to research conducted by Arora and Singh (2020). The short term discretionary accrual and underpricing characteristics are considered to have a positive effect on the level of oversubscription in accordance with the hypothesis based on signal theory. This study uses multiple regression analysis, normality test to fulfill multiple regression tests and other classical assumption tests as well as the fit and goodness test. This study found that the level of oversubscription can be influenced by earnings management and underpricing and has explained the relationship between the dependent and independent variables. The results of this study explain that short term discretionary accruals have a positive effect on the level of oversubscription of the IPO of SMEs. Abnormal cash flow has a significant negative effect on the level of oversubscription. Meanwhile, long term discretionary accrual, abnormal discretionary expense, underpricing have no effect on the level of oversubscription of the IPO of SMEs in Indonesia.